Attaining Moral Knowledge in the Church and Models of Adult Learning - Shields, Richard (Catholic Education: A Journal of Inquiry and Practice, 2009)
For the Holy See this signifies a loss of a sense of sin and reconciliation, rightly connecting moral consciousness and faith in salvation with sacramental celebration. Cultural studies underscore the importance of ritual practices as an essential element of religion’s ability to deal with the experience of moral evil. However, decline in the frequency of confession may also be complicated by indifference among North American Catholics to current roles and power relations in the Church. In light of moral individualism in society and new ways of envisioning the Church fostered by Vatican II, the challenge of moral education in the Church is complex, but hopeful. Effective religious education, responsive to the situation of contemporary Catholics, will seek innovative approaches that are rooted in the tradition and developed in communities of living faith. The essay suggests that theories of transformative learning and communities of practice offer helpful models for responding to the crisis of sin and reconciliation in Roman Catholicism.